Productivity Analysis Using Methods David J. Sumanth - Faturrahman, Yudi (Universitas Putra Indonesia YPTK Padang, 2025)
Productivity cycle analysis is a necessity for every company, it is intended to determine the level of performance that has been set and as an evaluation for performance improvement in the future. The problem that occurs is that the level of productivity fluctuates and there is a decrease in the productivity index, where the value of input goes up and output goes down. The purpose of this study is to determine the measurement of productivity and productivity index and how to increase the productivity. The method proposed is David J. Sumanth. The data used are input and output data. The results obtained are the productivity level of total output and input for the first period of 2.90%, the second period of 2.79%, the third period of 2.88%, the fourth period of 3.33% and the fifth period of 3.06%. The figures obtained from the productivity calculation show that each month the ratio of output and input is still not balanced. The highest index occurred in 2020 at 1.16% and the lowest index occurred in 2018 at 0.97%. This is because the partial input input also fluctuates.